The Influence of Liquidity, Profitability, Company Size and Leverage on Dividend Policy in Big Trading Companies (Wholesale) Listed on the IDX - Devi Asari Manik; Ega Hanaya Syalomita Br Ginting (Journal Research of Social Science, Economics, and Management, 2022)
Companies need weapons to compete in the market, so they need to survive in business competition. Companies need a lot of money and must be able to manage the resources needed to produce optimal results. This program aims to analyze whether liquidity, profitability, firm size and leverage affect dividend policy, either partially or simultaneously. The research method used is descriptive analysis method and multiple linear regression analysis. The population in this study amounted to 29 companies listed on the Indonesia Stock Exchange. The data used in this study were obtained through the website www.idx.co.id and the company's official website. The results showed that partially Current Ratio had a significant effect on the Dividend Payout Ratio, Return on Assets had a significant effect on the Dividend Payout Ratio, Company Size had a significant effect on the Dividend Payout Ratio and Debt to Equity Ratio had a significant effect on the Dividend Payout Ratio. Simultaneously Current Ratio, Return on Assets, Company Size and Debt to Equity Ratio have a significant effect on the Dividend Payout Ratio.